2008
DOI: 10.1111/j.1537-2995.2008.01778.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mirasol PRT treatment on storage lesion development in plasma‐stored apheresis‐derived platelets compared to untreated and irradiated units

Abstract: Although storage variables clearly showed the effects of PRT treatment, apheresis PLTs treated with Mirasol PRT retained cell quality during 5 days of storage without loss of mitochondria-based oxidative respiration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
91
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(108 citation statements)
references
References 38 publications
16
91
0
1
Order By: Relevance
“…As compared to untreated C units, the lower annexin V release of M units combined with higher HSRs, at least until storage day 5, could have resulted from differences in glucose metabolism, leading to better energy maintenance after PRT treatment with riboflavin-UVB. As reported previously, compared to untreated PLTs, riboflavin-UVB-treated PLTs exhibited an obviously up-regulated mitochondria-based respiration [25], which delivers profoundly more ATP than the anaerobic glycolytic pathway. On the other hand, PRT treatment with the psoralen-based technology appeared to impair oxidative phosphorylation [26].…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…As compared to untreated C units, the lower annexin V release of M units combined with higher HSRs, at least until storage day 5, could have resulted from differences in glucose metabolism, leading to better energy maintenance after PRT treatment with riboflavin-UVB. As reported previously, compared to untreated PLTs, riboflavin-UVB-treated PLTs exhibited an obviously up-regulated mitochondria-based respiration [25], which delivers profoundly more ATP than the anaerobic glycolytic pathway. On the other hand, PRT treatment with the psoralen-based technology appeared to impair oxidative phosphorylation [26].…”
Section: Discussionsupporting
confidence: 48%
“…Evaluation of PLT count, contamination with red and white blood cells via flow cytometry, LDH release, HSR, and bacterial contamination with the Bactec ® culturing system (Becton Dickinson, San Jose, CA, USA) were performed as described previously [25,26]. The pH value was analyzed at 37 °C on an automated blood gas analyzer (Rapidlab 1260, Siemens Medical Solutions Diagnostics mbH, Fernwald, Germany) and corrected to 22 °C.…”
Section: Analysis Of Cell Count Ldh Release Ph Hypotonic Shock Resmentioning
confidence: 99%
“…[8][9][10] Mitochondrial membrane depolarization occurs in PCs during blood bank storage and further increases upon PI treatment. [11][12][13] Recently, we and other groups have demonstrated that apoptotic events including phosphatidylserine (PS) exposure, increased proapoptotic protein expression, and caspase activation are triggered by RF/UV treatment in stored PCs, further supporting the model that apoptosis is involved in development of the PLT storage lesion. 14,15 However, the detailed biochemical mechanism(s) triggered by RF/UV are still unclear.…”
mentioning
confidence: 84%
“…A number of studies have concluded that Mirasol treatment exacerbates the effects of the platelet storage lesion, resulting in increased glucose consumption, lactate production, and increased markers of platelet activation [2,3,4,5,6]. Further, we and others have previously demonstrated that Mirasol treatment affects platelet signal transduction and apoptotic protein expression [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%